2011
DOI: 10.1007/s00590-011-0856-0
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic acromioclavicular joint reconstruction using a synthetic ligament device

Abstract: Purpose To describe an all-arthroscopic treatment of acromioclavicular joint (ACJ) dislocation and report the clinical results of the procedure. Methods This study consisted of 54 patients of whom 49 were men and 5 were women. The age of the patients averaged 39 years (range 16-69 years). All the symptomatic acute and chronic acromioclavicular joint dislocations classified according to Rockwood type III-IV were included in the study. All of them underwent standard clinical and radiological examination. Result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Eleven articles reported residual shoulder, hardware irritation, or ACJ pain as a postoperative complication with a pooled rate of 26.7% (95% CI: 17.8%–36.6%; I 2 =57.2%) ( Figure 3 ). Kany et al 20 reported six patients who experienced postoperative capsulitis and night pain. Each of these cases ultimately resolved with medical management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven articles reported residual shoulder, hardware irritation, or ACJ pain as a postoperative complication with a pooled rate of 26.7% (95% CI: 17.8%–36.6%; I 2 =57.2%) ( Figure 3 ). Kany et al 20 reported six patients who experienced postoperative capsulitis and night pain. Each of these cases ultimately resolved with medical management.…”
Section: Resultsmentioning
confidence: 99%
“… 10 Furthermore, there have been multiple reports of significant complication rates using arthroscopic or arthroscopically assisted techniques including: hardware erosion into the clavicle in over 40% of cases; 19 hardware failures in 70% of cases; 10 and, less commonly, persistent pain, infection, clavicle or coracoid fracture, CC calcification, and shoulder stiffness. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…However, the proximity of some important neurovascular structures, particularly the suprascapular nerve and the suprascapular artery, must always be remembered. On the other hand, there are also other less frequent complications, such as infection, that are usually superficial, post-operative capsulitis and pain, particularly night pain, 37 irritation over the superior aspect of the implant and CC calcification.…”
Section: Arthroscopic Techniquementioning
confidence: 99%
“…The same surgical technique is used for early and delayed surgery in four studies [9,10,19,23]. These four surgical techniques include hook plate technique, coraco-clavicular (CC) reconstruction with lArS, Dewar-Barrington …”
Section: Surgical Techniquementioning
confidence: 99%